HOUSE OF RAMINTEN SEBAGAI DAYA TARIK WISATA KULINER CERMINAN BUDAYA ASLI YOGYAKARTA - Jeremy Fitzgerald Kevin Parimo; Rakhmat Ashartono (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
House Of Raminten is a traditional restaurant from the city of Yogyakarta that serves modified Javanese food and drinks. House Of Raminten was created by an artist from Yogyakarta, namely Mr. Hamzah Sulaeman. The hallmark of the House Of Raminten is to use the concept of Javanese culture in every ornament in the building and to use traditional clothes for the waiters on duty. This method is used so that the typical Javanese culture is maintained and known by many people. Not only the use of concepts that attract tourists, the culinary served is also an attraction for tourists who visit because the prices are cheap but still provide the best quality. Culinary appeal and the use of Javanese cultural concepts are two strong things that are still maintained by House Of Raminten to maintain its uniqueness and invite tourists to visit this restaurant.Keywords: House Of Raminten, Culinary, Attraction, Culture